Oxford Wordpower Dictionary - Wehmeier, Sally (ed.) (Oxford, Oxford University Press, 1993)
Summary:Updated with over 500 new words, phrases and meanings, Oxford Wordpower Dictionary is a corpus-based dictionary that provides the tools intermediate learners need to build vocabulary and prepare for exams. Keyword entries show the most important words to know in English. This edition includes new Topic Notes, Exam Tips and Writing Tips, and a 16-page Oxford Writing Tutor. Students can search the A-Z dictionary by word or topic.
Donated by: Student
Keywords: dictionaries -- English language dictionaries -- wordpower -- quiz -- vocabulary